2020
DOI: 10.1038/s41392-020-00408-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of whey protein on viral infection and replication of SARS-CoV-2 and pangolin coronavirus in vitro

Abstract: Since severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA has been detected in human breastmilk, infants' safety with breastmilk feeding is of great concern for women with coronavirus disease 2019 (COVID-19). 1 It is known that milk has antiviral properties. 2 However, little is known about the antiviral property of human breastmilk to SARS-CoV-2 and its related pangolin coronavirus (GX_P2V). Here we present for the first time that whey protein from human breastmilk effectively inhibited both SARS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 5 publications
1
41
0
Order By: Relevance
“…Recent evidence indicates that breastfeeding does not seem to be associated with neonatal SARS-CoV-2 infection because viral transmission through the milk, if any, should be rare [23] and because a robust sIgA-dominant SARS-CoV-2 antibody response is detectable in human milk soon after infection in a significant majority of individuals [24], suggesting a possible protection granted by the mothers to their infants [25][26][27][28][29][30]. Moreover, there is evidence in vitro suggesting whey proteins in human breastmilk as a direct-acting inhibitor of SARS-CoV-2 infection and replication [31]. While it was demonstrated that a healthy mother-infant dyadic process positively impacts the infants' behavioral, cognitive, and socioemotional development [32], the possible long term effects of neonatal SARS-CoV-2 early infection, including neurological implications, are obviously unknown [33].…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence indicates that breastfeeding does not seem to be associated with neonatal SARS-CoV-2 infection because viral transmission through the milk, if any, should be rare [23] and because a robust sIgA-dominant SARS-CoV-2 antibody response is detectable in human milk soon after infection in a significant majority of individuals [24], suggesting a possible protection granted by the mothers to their infants [25][26][27][28][29][30]. Moreover, there is evidence in vitro suggesting whey proteins in human breastmilk as a direct-acting inhibitor of SARS-CoV-2 infection and replication [31]. While it was demonstrated that a healthy mother-infant dyadic process positively impacts the infants' behavioral, cognitive, and socioemotional development [32], the possible long term effects of neonatal SARS-CoV-2 early infection, including neurological implications, are obviously unknown [33].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth commenting that all the nurses who took part in this initiative provided excellent feedback (even though some of them had initial apprehensions), and now the Mazandaran regional maternity unit offers a telelactation program to mothers who remain in isolation with infants admitted to NICU. Recent reports about the inhibitory capacity of breast milk against COVID-19 [ 18 ] give additional impetus to our approach, which has the potential transferability to resource-limited settings. The previous experience of the unit in achieving induction of lactation in challenging clinical scenarios through international collaborative efforts [ 19 ] also provided confidence to our neonatal team to pursue a low-cost mobile phone-enabled e-lactation in the midst of a pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…However, other researchers have verified that the main antimicrobial components of breast milk, such as LF and IgA antibody, showed limited anti-coronavirus activity, but whey protein is a direct-acting inhibitor of SARS-CoV-2 infection by blocking viral attachment, entry, and even post-entry viral replication. This suggests that other factors of breast milk may play the important anti-COVID-19 role (243). Even with the limits of a preliminary and preprint report, and with the necessity of further investigation of its molecular mechanism of action in the context of SARS-CoV-2 infection, the data are interesting.…”
Section: Virus Invasion Replication and Releasementioning
confidence: 98%